Association of GPX1 Pro198Leu and SOD1 A251G Polymorphisms With Risk of Acute Kidney Rejection - Rayatpisheh, Shima; Karimi, Mohammad-Hossein; Saadat, Iraj (Scripta Medica, 2025)
Background/Aim: Acute rejection is one factor threatening the success of kidney transplantation. One of the factors that can cause graft rejection is oxidative stress. The aim of this study was to investigate the association between GPX1 Pro198Leu and SOD1 A251G polymorphisms and acute renal allograft rejection. Methods: A total of 262 healthy individuals and 262 patients who had undergone kidney transplantation were enrolled in the present study, of which 46 patients had acute rejection. The genotypes were determined using the PCR-RFLP technique. Case-control study between patients and control groups and cohort study between patients with and without acute rejection were then performed. Results: Analysis showed that the incidence of kidney disease leading to kidney transplantation did not depend on the genotype of GPX1 and SOD1 polymorphisms. In the cohort study, no significant differences were observed between the cases with and without acute rejection for any of the two genes. Conclusions: The genotypes of GPX1 and SOD1 polymorphisms were not found to be involved in the incidence of acute renal rejection. It is advised to continue further studies, because defects in the activities of these genes can be compensated by other members of their families.